2020
DOI: 10.5483/bmbrep.2020.53.3.016
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of transient receptor potential (TRP) channels in cancer progression

Abstract: Transient receptor potential (TRP) channels comprise a diverse family of ion channels, the majority of which are calcium permeable and show sophisticated regulatory patterns in response to various environmental cues. Early studies led to the recognition of TRP channels as environmental and chemical sensors. Later studies revealed that TRP channels mediated the regulation of intracellular calcium. Mutations in TRP channel genes result in abnormal regulation of TRP channel function or expression, and interfere w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 104 publications
0
60
0
4
Order By: Relevance
“…In recent years, the involvement of Ca 2+ -permeable channels in neoplastic diseases has been extensively investigated and a direct correlation between their dysregulation and cancer development has been shown ( Monteith et al, 2017 ). Among them, Transient Receptor Potential (TRP) channels have revealed an important involvement in the regulation of many signaling pathways associated with tumor progression ( Yang and Kim, 2020 ). One of the key features of TRP channels is their polymodal activation mechanism and their involvement in different signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the involvement of Ca 2+ -permeable channels in neoplastic diseases has been extensively investigated and a direct correlation between their dysregulation and cancer development has been shown ( Monteith et al, 2017 ). Among them, Transient Receptor Potential (TRP) channels have revealed an important involvement in the regulation of many signaling pathways associated with tumor progression ( Yang and Kim, 2020 ). One of the key features of TRP channels is their polymodal activation mechanism and their involvement in different signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, MMP-2 and MMP-9 are considered the most important in metastasis, since they were often aberrantly expressed in tumors ( Jabłońska-trypuć et al, 2016 ). Both TRP channels and small GTPases have been implicated in increased tumor invasiveness through the induction of MMPs expression ( Betson and Braga, 2003 ; Yang and Kim, 2020 ). Indeed, TRPM2, TRPM7, TRPM8, TRPV2, and TRPC1 have shown to cause upregulation of MMP9 in a Ca 2+ -dependent manner in gastric, bladder, oral squamous, prostate and thyroid cancer cells respectively ( Monet et al, 2010 ; Okamoto et al, 2012 ; Asghar et al, 2015 ; Cao et al, 2016 ; Chen L. et al 2017 ; Chen Z. et al, 2017 ; Almasi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, TRPM7 is highly expressed in OC cells and tissues and its expression level is significantly associated with poor prognosis in patients with OC [189]. Silencing of TRPM7 with siRNA inhibited OC cells proliferation, migration, and invasion, through direct regulation of calcium influx that, in turn, modulates many signaling transduction pathways including Akt, Src, and p38 ( Figure 1) [190,191].…”
Section: Trp Channelsmentioning
confidence: 99%
“…Thus, its cellular level is always subjected to tight regulations, mainly by the activity of three plasma membrane Ca 2+ channels, voltage-gated Ca 2+ channels, Orai-mediated store-operated channels, and transient receptor potential-mediated Ca 2+ channels. It has been revealed that disruption in the expression or function of these channels is often correlated with carcinogenesis and/or chemoresistance [119,120]. Hence, targeting their expression level or function may serve as an effective strategy to improve cancer treatment.…”
Section: Ca 2+ Channelsmentioning
confidence: 99%